2010
DOI: 10.1039/b9nj00503j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of halonorbornane and oxo-substituted derivatives with different anions by the electron transfer mechanism; redox catalysis in stabilized radicals

Abstract: Reactions of 2-bromo-, 2-chloronorbornane, 3-chloronorbornan-2-one and 3-bromocamphor with Me 3 Sn À , Ph 2 P À or PhS À ions were studied by an S RN 1 mechanism in liquid ammonia or DMSO. The results show that substrates having a carbonyl group facilitate electron transfer reactions, which are impeded in the absence of such a group. However, when the free radical formed is stabilized by conjugation, the coupling reaction decreases, causing a concomitant increase in the reduction product. Theoretical studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…2 Consequently, the oxogroup may enhance the initiation steps by redox catalysis, allowing the formation of radicals. On the other hand, we have described the reactivity of 3-camphoryl radicals with diverse nucleophiles 3 and showed that those conjugated radicals can delay the coupling reactions due to their stability. 3 Other examples involving conjugated radicals have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Consequently, the oxogroup may enhance the initiation steps by redox catalysis, allowing the formation of radicals. On the other hand, we have described the reactivity of 3-camphoryl radicals with diverse nucleophiles 3 and showed that those conjugated radicals can delay the coupling reactions due to their stability. 3 Other examples involving conjugated radicals have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we have described the reactivity of 3-camphoryl radicals with diverse nucleophiles 3 and showed that those conjugated radicals can delay the coupling reactions due to their stability. 3 Other examples involving conjugated radicals have been reported. For instance, p-nitro-1,1-dimethylphenacyl chloride afforded substitution products with 2-nitropropane, diethyl malonate or diethyl methylmalonate anions via the S RN 1 process, whereas classical substitutions were observed when PhSor p-MeC 6 H 4 SO 2 ions were used.…”
Section: Introductionmentioning
confidence: 99%